Focusing on climate-related internal displacement - Leckie, S; Simperingham, E (Refugee Studies Centre, University of Oxford, 2015)
Global attention should place a primary focus on the application of best practice and the development of innovative initiatives to solve climate-related internal displacement, rather than on grappling with the far rarer movements of people across borders.